An Analysis of Pronoun in “Cinderella” Story by Disney - Saragih, Dhea; Situmorang, Maria Magdalena (CV. Tripe Konsultan, 2023)
This research aims to analyze pronouns used in a story with title “Cinderella” by Disney. Researchers chose descriptive qualitative method to analyze the data in order to show pronouns that appeared in the story of Cinderella. There were several steps that researchers conducted to collect data, including read the story, then identified the pronouns, and finally analyzed each pronoun from the story descriptively. This research found that there were 15 pronouns used in the story of Cinderella with six types of pronoun. These pronouns include 5 personal pronouns as subject (They, She, It, He, and I), 2 personal pronouns as object (her and them), 3 possessive adjectives (her, his, and their), 2 relative pronouns (whose and who), 2 demonstrative pronouns (this and that), and 1 indefinite pronoun (everyone). In addition, the pronoun that appeared the most was “her” as much as 22.92%, and conversely, pronoun that appeared the least were “their, this, whose, I, everyone, and who”, which each of them only appeared 1 time in the story (2.08% for each pronoun).